Synthesis of trimetallic oxide (Fe2O3–MgO–CuO) nanocomposites and evaluation of their structural and optical properties - A. H. Al-Hammadi; Adnan Alnehia; Annas Al-Sharabi; Hisham Alnahari; Abdel-Basit Al-Odayni (Scientific Reports, 2023)
Abstract In this paper, tri-phase Fe2O3–MgO–CuO nanocomposites (NCs) and pure CuO, Fe2O3 and MgO nanoparticles (NPs) were prepared using sol–gel technique. The physical properties of the prepared products were examined using SEM, XRD, and UV–visible. The XRD data indicated the formation of pure CuO, Fe2O3 and MgO NPs, as well as nanocomposite formation with Fe2O3 (cubic), MgO (cubic), and CuO (monoclinic). The crystallite size of all the prepared samples was calculated via Scherrer's formula. The energy bandgap of CuO, Fe2O3 and MgO and Fe2O3–MgO–CuO NCs were computed from UV–visible spectroscopy as following 2.13, 2.29, 5.43 and 2.96 eV, respectively. The results showed that Fe2O3–MgO–CuO NCs is an alternative material for a wide range of applications as optoelectronics devices due to their outstanding properties.